Unequal Civic Development? Vocational Tracking and Civic Outcomes in Germany - Corey Savage; Michael Becker; Jürgen Baumert (SAGE Publishing, 2021)
Vocational education and training (VET) is a common form of upper secondary school tracking in countries around the world. There are ongoing debates regarding the effects of this differentiation on academic and labor market outcomes; however, evidence on civic outcomes is lacking. Using a unique cohort study in Germany ( N = 2461) and a doubly robust weighting approach with a rich set of baseline covariates to address selection bias, we estimated the effects of VET (relative to academic upper secondary school) on political interest, internal political efficacy, and intent to vote across 15 years of late adolescence and early adulthood. We estimated negative effects of VET on these civic outcomes, particularly as participants grew older. Implications for future research and VET policy are discussed.